Correlation of motivations for selfie-posting behavior with personality traits - Chaudhari, Bhushan Laxman (Ind Psychiatry J, 2019)
BACKGROUND: The widespread popularity of selfie-posting behavior has led to increasing academic interest in exploring psychological determinants for this behavior. AIM: The study aimed to evaluate sociodemographic factors, personality traits, and psychological motivations associated with selfie-posting behavior and to evaluate the association of psychological motivations for selfie-posting with personality traits. MATERIALS AND METHODS: This cross-sectional study assessed 727 medical and physiotherapy students with a semi-structured questionnaire consisting of information about sociodemographic factors, selfie-posting, and editing behavior, the Big Five Inventory and motivations for selfie-posting scale. RESULTS: There was a positive correlation of female gender, extraversion, and agreeableness with selfie-posting and editing and a negative correlation of neuroticism with both types of behavior. Communication was the most common motivation for selfie-posting followed by attention seeking. Extraverted people post selfies for attention seeking, communication, and archiving motive while agreeable individuals post them only for communication and archiving. CONCLUSION: Females as well as individuals with high extraversion and agreeableness engage in selfie-posting and selfie-editing more frequently while neurotic individuals tend to avoid engaging this behavior. Motivation for posting selfies most commonly was for communication followed by attention seeking. Individuals with different personalities use selfies differently to fulfill their inner psychological needs.